Dating jitters - Tay, Ashley Rui Yi (2018)
Dating Jitters is a short romantic comedy Visual Effects (VFX) film depicting the personification of one’s nervousness during a first date. The premise is that two long-time friends, who like each other, go on their first romantic date, with the added twist that they have “nervous monsters”, a physical representation of their nervousness. The sizes of the monsters are proportional to the level of nervousness in their owners, and will cause more chaos as they get bigger. Throughout the date, our protagonists try to hide their monsters from each other, similarly to how one would try to hide their nervousness on a first date.